Heaven, Texas - Phillips, Susan Elizabeth; Copyright Paperback Collection (Library of Congress) (New York, N.Y. : Avon Books, 1995)
Come heck or high water, Gracie Snow is determined to drag the legendary ex-jock Bobby Tom Denton back home to Heaven, Texas, to begin shooting his first motion picture. But bad boy Bobby has no plans to cooperate with the prim and bossy Ohio wallflower whom he can't get off his mind or out of his life.
Keywords: Motion pictures -- Production and direction -- Fiction; Football players -- Fiction; Actors -- Fiction; Texas -- Fiction; Love stories